C4N8O6: A Promising Ternary CNO‐Compound With Good Detonation Performance And Low Sensitivity. Issue 8 (28th May 2021) - Li, Xin; Wang, Qian; Zhang, Shujia; Lin, Qiuhan; Lu, Ming
Abstract: Among energetic materials, there is a significant challenge facing researchers: to seek an optimal balance between detonation performance and molecular stability. By introducing an azo1, 2, 4‐oxadiazole backbone and low‐sensitivity C‐NO2 moieties, a promising energetic molecule, 1, 2‐bis(3‐nitro‐1, 2, 4‐oxadiazol‐5‐yl)diazene (4) was prepared through three‐step reaction and well‐characterized by IR and multinuclear NMR spectroscopy, DSC measurement, elemental analysis, and single‐crystal X‐ray diffraction. It shows high thermal stability (Td =260 °C), good mechanical sensitivity (IS: 21 J, FS: 220 N), and superior detonation performance (D: 9336 m s −1, P: 37.7 GPa). The combination of advanced performance and desirable safety as well as the simple reaction process make it highly competitive in the field of energetic materials. Abstract :